Effect Of Tannins In Commonly Fed Fodders On Nutrient Availability In Goats - Ally K (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 1994)
The effect of nature and level of tannins in tree leaves on nutrient utilisation in animals was investigated using six adult non producing Saanen x Malabari female goats. Four commonly fed tree leaves viz., subabul, jack, venga and banana leaves selected on the basis of their tannin contents as well as palatability and local availability were used for the feeding experiments. The experimental animals were maintained on the respective fodders as the sole feed, each for a period of about one month under identical managemental conditions. A digestion cum metabolism trial was carried out at the end of each feeding experiment. The data on body weight, average dry matter intake, digestibility coefficients of nutrients, balance of nitrogen, calcium and phosphorus and haematological values gathered during the experimental period were taken as the criteria for evaluating the effect of tannins on nutrient availability in goats. The total tannin content in the different tree leaves studied ranged from 2.6 to 7.8 per cent, with condensed tannins predominating in majority of the fodders. The average dry matter consumption (g/ kg metabolic live weight) of goats when fed jack and subabul leaves with 4.0 percent and 5.5 percent total tannins respectively on dry matter basis were higher than when fed venga and banana leaves with 4.7 and 3.7 percent respectively of the same. The digestibility coefficients of dry matter, crude protein, crude fibre, ether extract and nitrogen free extract in banana leaves with the lowest level of total and condensed tannins (3.7 percent and 1.6 percent respectively) were higher than in jack, subabul and venga leaves, the differences between the various leaves in this regard being not statistically significant, excepting for nitrogen free extract. Though all the experimental animals maintained positive balances for nitrogen, the average nitrogen balance (g per day) was higher in goats fed jack leaves when compared to those given subabul, venga and banana leaves as the sole feed. The animals fed all the four fodders maintained positive balances for calcium, the balance in goats fed subabul being significantly higher than those given the other fodders. Though a negative phosphorus balance was recorded in goats fed subabul and venga leaves, the animals on jack and banana leaves as the sole fodder maintained positive balances for phosphorus. The haematological constituents Viz., haemoglobin, plasma protein, calcium and phosphorus in goats fed the four fodders were all well within the normal ranges for the species. A critical assessment of the overall results obtained during the course of the present study indicates that even a level of upto 5.5 percent of total tannins and 3.4 percent of condensed tannins in tree leaves does not appear to exert any deleterious effect on feed consumption and nutrient utilisation in goats.